Engaging Students Actively for Effective Teaching-Learning - Kolhekar, Megha; Shah, Milind; Jadjav, Anita (Journal of Engineering Education Transformations, 2021)
Due to the current pandemic situation all across the world, the education sector is undergoing a transformation. Engineering education is changing its face, too, as it is the need of the hour to impart knowledge and skills remotely to the students. At our Institute, we had not attempted the online teaching-learning methodology before the pandemic because students daily travelled to the Institute, and the need did not arise. Currently, we have adapted to MS Teams as our online platform for the conduction of classes and software laboratories. The major challenge in online teaching is to engage the students actively and ensure that learning is happening. Active learning is defined as â€œeducational methods in which students are involved in higher-order thinking (analysis, synthesis, evaluation).â€ This work is a report on the methodologies adopted by the authors in the ongoing semester, involving some of the well-documented active learning strategies for two undergraduate courses in Mumbai University curriculum. The paper describes the adopted teaching methodologies with statistics collected during the ongoing semester and summarizes the outcomes of these experiments in terms of studentsâ€™ â€œLearning Coefficient (LC)â€ in the undertaken courses based on the feedback collected by the course coordinators. Learning Coefficient is a number between 0 to 1 where 0 indicates non-interactive sessions and 1 indicates the highly interactive and highest level of learning. In this paper, we report a learning coefficient of 0.7 for one course and 0.64 for the other course through active learning techniques. These coefficients are indicative of â€œlearning happeningâ€.